Diseño de una colección de indumentaria para la práctica del ciclismo en la empresa Texcrip - Pilco Criollo, Shirley Milena (2025)
This integrative project focuses on the design of a specialized clothing collection for cycling. Currently, the local market lacks affordable and quality options, as most clothing is imported and has high prices, which limits access to suitable products for cyclists, especially those who are just starting out in this activity. Cycling has increased in popularity as a recreational activity and a sustainable means of transportation, promoting healthier lifestyles and contributing to the reduction of traffic and pollution. However, the lack of suitable and affordable clothing represents a considerable obstacle, particularly for novice cyclists who want to enjoy the experience without incurring exorbitant expenses. Texcrip's proposal seeks to address this problem by offering a line of clothing that meets the functional needs of cyclists and is economically accessible to a wide audience. The main objective of this project is to develop a collection that prioritizes essential aspects such as comfort, aerodynamics and durability. To this end, a thorough market analysis and a detailed study of the preferences and needs of local cyclists will be carried out. This approach will allow us to identify the features most valued by users, ensuring that each garment meets the standards required for an optimal cycling experience. In conclusion, this project aims to transform the perception and practice of cycling in the region, positioning Texcrip as a benchmark in cycling apparel and providing local cyclists with the necessary tools to fully enjoy their passion.